Internet Machine Prototype with a Coin Payment Using a Rock Pi Microcontroller - Azhar, Raisul; Santoso, Heroe; Hariyadi, I Putu; Husain, Husain; Afriandi, Mahsus (Jurnal Bumigora Information Technology (BITe), 2024)
Background: Coins are widely used in game machines to play game applications. Internet use is usually done by purchasing an internet package. This method is often used, but coins are rarely used.Objective: The aim of this research is how to make a machine that is capable of using coins as internet payment, especially hotspots.Methods: The research method was carried out using an experimental method with stages of analysis, prototype design, and testing using a descriptive approach.Result: This research produced 1 one-unit prototype machine equipped with an application for internet hotspots by inserting IDR 500 and IDR 1000 coins with connection limits according to the value of the coins entered.Conclusion: This research produces prototypes and coin internet application software.